Medical Monitoring for Occupational Asthma Among Toluene Diisocyanate Production Workers in the United States. (December 2017) - Cassidy, Laura D.; Doney, Brent; Wang, Mei Lin; Kurth, Laura; Conner, Patrick R.; Collins, James J.; Carson, Michael; Molenaar, Don; Redlich, Carrie A.; Storey, Eileen
Abstract : Objective: The aim of this study was to describe a study of medical monitoring methods and lessons learned in detecting health outcomes in U.S. plants producing toluene diisocyanate (TDI). Methods: A multidisciplinary team implemented a medical and environmental monitoring program in three TDI plants. Results: Of 269 eligible workers, 197 (73%) participated and 42 (21%) met symptom and/or lung function criteria that would trigger evaluation for possible asthma over 5 years of data collection. Subsequent evaluation was delayed for most, and a web-based data collection system improved timeliness. Conclusion: Medical monitoring of TDI workers identified workers triggering further assessment per study protocol. Systems and/or personnel to ensure rapid follow-up are needed to highlight when triggering events represent potential cases of asthma needing further evaluation. Implementation of a research protocol requires resources and oversight beyond an occupational health program.